Antibiotic-laden bone cement for diabetic foot infected wounds: A systematic review and meta-analysis - Dong, Tingting; Huang, Qi; Sun, Zengmei (Frontiers in Endocrinology, 2023)
Objective A large body of literature has demonstrated the significant efficacy of antibiotic bone cement in treating infected diabetic foot wounds, but the corresponding evidence-based evidence is less. Therefore, this article provides a meta-analysis of the effectiveness of antibiotic bone cement in treating infected diabetic foot wounds to provide a reference basis for clinical treatment. Methods PubMed, Embase, Cochrane library, Scoup, China Knowledge Network (CNKI), Wanfang database, and the World Health Organization (WHO) International Clinical Trials Registry platform (ClinicalTrials.gov) were searched, and the search time was from the establishment of the database to October 2022, and two investigators independently The data from eligible studies were screened, the quality of the literature was evaluated using the Cochrane Evaluation Manual, and statistical analysis was performed using RevMan 5.3 software. Results A total of 9 randomized controlled studies (n=532) were included, and compared with the control group, antibiotic bone cement treatment reduced the time to wound healing (MD=-7.30 95% CI [-10.38, -4.23]), hospital stay (MD=-6.32, 95% CI [-10.15, -2.48]), and time to bacterial conversion of the wound (MD=-5.15, 95% CI [-7.15,-2.19]); reduced number of procedures (MD=-2.35, 95% CI [-3.68, -1.02]). Conclusion Antibiotic bone cement has significant advantages over traditional treatment for diabetic foot wound infection and is worthy of clinical promotion and application. PROSPERO registration number CDR 362293